Pichuco and his “eraser”: differences between text and execution in a tango arranged by Astor Piazzolla for the typical Aníbal Troilo orchestra (Revista Argentina de Musicología, 2019)
In the introduction of a tango interpreted by Aníbal Troilo and his typical orchestra, I aurally recognize the use of the topos of the guitar. When I access the manuscript of that arrangement, I discover that the introduction was crossed out and that the original writing differs from the recorded performance. When verifying that the arrangement is signed by Astor Piazzolla and that in the historiographies he does not appear as the author, I become aware that it is a primary source of great testimonial value. The contrast of the text and its secondary annotations with its two recorded versions, have diversified the research and redefined the initial object of study. What in principle was an analytical approach to a compositional resource, becomes a journey through various research methodologies that the document proposes.This article is a case study on the operation of the arrangement and the interpretive praxis in the typical tango orchestra. Troilo as director and Piazzolla as arranger, two of the most important musicians in the history of the genre, are studied in this work providing significant information on the reception and conformation of tango styles in his golden age
Keywords: arrangements; performance practice; modernity; topics; golden age